Polymorphisms of Antigen-Presenting Machinery Genes in Non-Small Cell Lung Cancer: Different Impact on Disease Risk and Clinical Parameters in Smokers and Never-Smokers - Wiśniewski, Andrzej; Sobczyński, Maciej; Pawełczyk, Konrad; Porębska, Irena; Jasek, Monika; Wagner, Marta; Niepiekło-Miniewska, Wanda; Kowal, Aneta; Dubis, Joanna; Jędruchniewicz, Natalia; Kuśnierczyk, Piotr (Frontiers in Immunology, 2021)
Lung cancer is strongly associated with cigarette smoking, nevertheless some never-smokers develop cancer. Immune eradication of cancer cells is dependent on polymorphisms of HLA class I molecules and antigen-processing machinery (APM) components. We have already published highly significant associations of single nucleotide polymorphisms (SNPs) of the ERAP1 gene with non-small cell lung cancer (NSCLC) in Chinese, but not in Polish populations. However, the smoking status of participants was not known in the previous study. Here, we compared the distribution of APM polymorphic variants in larger cohorts of Polish patients with NSCLC and controls, stratified according to their smoking status. We found significant but opposite associations in never-smokers and in smokers of all tested SNPs (rs26653, rs2287987, rs30187 and rs27044) but one (rs26618) in ERAP1. No significant associations were seen in other genes. Haplotype analysis indicated that the distribution of many ERAP1/2 haplotypes is opposite, depending on smoking status. Additionally, haplotypic combination of low activity ERAP1 and the lack of an active form of ERAP2 seems to favor the disease in never-smokers. We also revealed interesting associations of some APM polymorphisms with: age at diagnosis (ERAP1 rs26653), disease stage (ERAP1 rs27044, PSMB9 rs17587), overall survival (ERAP1 rs30187), and response to chemotherapy (ERAP1 rs27044). The results presented here may suggest the important role for ERAP1 in the anti-cancer response, which is different in smokers versus never-smokers, depending to some extent on the presence of ERAP2, and affecting NSCLC clinical course.